Smart Card Key / Noor Iznina Abdul Aziz and Ku Noraini Ku Abdul Samad - Abdul Aziz, Noor Iznina; Ku Abdul Samad, Ku Noraini (2005)
A key is very important in our life for safety. In market today, there are diverse types of key. But Smart Card Key is a good for a smart home. It has safety characteristics and very privacy. For this project, Smart Card Key has 3 ICs will be used which are UM6, SN54/74LS240. Smart Card Key is design to be used in smart home and is also used for hotel rooms.